Cytoplasmic Beta and Gamma Actin Isoforms Reorganization and Regulation in Tumor Cells in Culture and Tissue - Dugina, V. B.; Shagieva, G. S.; Kopnin, P. B. (Frontiers in Pharmacology, 2022)
The cytoplasmic actins (β- and γ-) play crucial roles during key cellular processes like adhesion, migration, polarization, mitosis, and cytokinesis. Variations of actin isoforms are directly or indirectly linked to severe pathologies, so investigations of underlying mechanisms would be of major relevance not only for fundamental research but also for clinical applications. The disruption of actin cytoskeleton and intercellular adhesions contribute to the neoplastic transformation, as its important for the tumor growth and acquisition of invasive properties in the epithelial malignancies. Cytoplasmic β- and γ-actins display the functional diversity: β-actin plays a preferential role in contractile activities, whereas γ-actin participates mainly in the formation of a submembrane network necessary for the cell shape flexibility and motile activity. The involvement of β- and γ-actin in cell architecture, motility, division, and adhesion junctions in normal cells is not equivalent, and the major question was: «whether isoform expression and/or structural organization is related to pathological function». Significant results were obtained in cancer cells compared with normal cells in culture, in human malignant tissue sections, and via selective regulation of β- and γ-actins’ expression. Investigation of the actins’ diversity and function in cancers may help to choose the benefit treatment strategies, and to design new therapies.